Sociodemographic Determinants of Willingness and Extent to Pay for COVID-19 Vaccine in India - Kiran, Tanvi; Junaid, K. P.; Sharma, Divya; Jain, Lovely; Vij, Jatina; Satapathy, Prakasini; Chakrapani, Venkatesan; Patro, Binod Kumar; Kar, Sitanshu Sekhar; Singh, Ritesh; Pala, Star; Bali, Surya; et al. (Frontiers in Public Health, 2022)
Background: Responding to the fast transmission rates and increasing fatality rates, countries across the world expedited the development and deployment of the vaccine for the COVID 19. Evaluation of individuals’ Willingness to pay (WTP) would provide pertinent information regarding future demand and financing preferences, which shall help devise the effective payment strategy for the COVID-19 vaccination. Methods: A nationwide cross-sectional, self-administered online survey using a structured questionnaire was conducted to identify the socio-demographic determinants of willingness and extent to pay for the COVID vaccine in India. A non-probability convenience sampling followed by snowball sampling were employed to recruit participants (n=3341). The likelihood of socio-demographic determinants to predict willingness and extent to pay was modelled using multivariable binary logistic regression analysis. Results: Out of the 3371 participants, 68% (n=2271) were willing to pay for COVID vaccine. Results showed significantly higher odds for willingness to pay among participants who were single (aOR= 1.394, p<0.01), having a family size of 4 members (aOR=1.346, p<0.01). The adjusted odds sizably increased from 1.396 for participants whose monthly income was between INR 10000 to INR 20000/month to 2.240 for participants with monthly income above INR 50000/month. Further, out of the 2271 of those who were willing to pay for vaccine, majority (n=1246, 54.9%) were willing to pay below 50% of the vaccine cost. The study found those who are single (aOR= 0.688, , p<0.01), having an income between INR 20000 to 50000 per month (aOR= 0.686, p<0.05) and those who belonged to socially disadvantaged category (aOR= 0.450, p<0.01) were estimated to have significantly lower odds of willing to pay more than 50% of the COVID vaccine cost. Conclusion: This study observed that majority of those who willing to pay for vaccine were willing to pay only up to 50% of the vaccine and income was observed as a precursor predictor of the willingness and extent to pay for vaccine. The understanding on the willingness and extent to pay for vaccine and its sociodemographic determinants will be helpful for making the strategic decisions related to the financing of COVID vaccine in India.